Perspective of Melatonin-Mediated Stress Resilience and Cu Remediation Efficiency of Brassica juncea in Cu-Contaminated Soils - Mir, Anayat Rasool; Alam, Pravej; Hayat, Shamsul (Frontiers in Plant Science, 2022)
The present study evaluated the influence of melatonin (MEL) on copper toxicity in terms of morpho-physiological, microscopic, histochemical and stress resilience responses in Brassica juncea. Different levels of Cu (0, 30 or 60 mg kg-1) were given in air dried soil, and 25 days after sowing (DAS) plants were sprayed with (30, 40 or 50 µM) of MEL. The results demonstrated that under Cu stress, significant amount of Cu got accumulated in plant tissues, particularly in roots than in upper ground tissues, thereby suppressing the overall growth as evident from the decrease in tolerance index, photosynthesis, and increase in oxidative stress biomarkers (reactive oxygen species, malondialdehyde and electrolyte leakage content) and cell death. Interestingly, the follow-up treatment of MEL, mainly 40 µM, efficiently improved the physio-biochemical and growth parameters, sugar accumulation and metabolism. The potential of MEL in modulating Cu-stress is attributed to its involvement in enriching the nutrient levels, improving chloroplast and stomatal organization, besides lowering the oxidative stress via enhanced levels of antioxidants. MEL improved the Cu-reclamation potential in plants by enhancing the Cu-uptake and its translocation to aerial tissues. Principal component analysis showed that most of the morpho-physiological and growth attributes were positively linked with the MEL and negatively related to the Cu levels; whereas all the stress enhancing attributes showed a strong relation with the excessive Cu levels in soils. The present study suggested that MEL has the potential to improve the growth, photosynthesis resulting in improved stress resilience under Cu stress along with increased remediation capability of mustard for remediation of Cu-contaminated soils.